2015
DOI: 10.1186/s12889-015-1871-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-infection symptoms following two large waterborne outbreaks of Cryptosporidium hominis in Northern Sweden, 2010–2011

Abstract: BackgroundIn 2010–2011, two large waterborne outbreaks caused by Cryptosporidium hominis affected two cities in Sweden, Östersund and Skellefteå. We investigated potential post-infection health consequences in people who had reported symptoms compatible with cryptosporidiosis during the outbreaks using questionnaires.MethodsWe compared cases linked to these outbreaks with non-cases in terms of symptoms present up to eleven months after the initial infection. We examined if cases were more likely to report a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 22 publications
(35 reference statements)
2
41
0
1
Order By: Relevance
“…Eight hundred seventy-two of those subjects also took part in a questionnaire-based follow-up investigation [9], and, 25 January 2013, we invited those respondents to complete another follow-up questionnaire regarding post-infection symptoms during the 3 months preceding the day of answering the questionnaire. Responses were recorded until 25 February 2013, and hence the period of recorded post-infection symptoms in the Östersund study was 25 October 2012 to 25 February 2013.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight hundred seventy-two of those subjects also took part in a questionnaire-based follow-up investigation [9], and, 25 January 2013, we invited those respondents to complete another follow-up questionnaire regarding post-infection symptoms during the 3 months preceding the day of answering the questionnaire. Responses were recorded until 25 February 2013, and hence the period of recorded post-infection symptoms in the Östersund study was 25 October 2012 to 25 February 2013.…”
Section: Methodsmentioning
confidence: 99%
“…A follow-up evaluation of the affected population revealed that outbreak cases were more likely to have gastrointestinal and joint-related symptoms up to 11 months after the initial infection [9]. We performed an additional follow-up investigation of the study population in Östersund to ascertain whether the symptoms were persisting 2 years after the outbreak occurred.…”
Section: Introductionmentioning
confidence: 99%
“…I en studie av mennesker smittet med Giardia (vel å merke ikke i sammenheng med utbrudd) i USA ble det vist at ekstraintestinale symptomer var relativt vanlig (23). Det er også verdt å merke seg at det vannbårne utbruddet av kryptosporidiose i Östersund også ble assosiert med langvarige gastrointestinale symptomer og leddplager (24).…”
Section: Kan Giardia Gi Langvarige Helseplager?unclassified
“…Cryptosporidium spp has been recognized as the cause of large waterborne and food‐borne outbreaks of gastroenteritis with long term complications and long‐lasting symptoms . C. spp .‐associated diarrhea has become well known as a result of the severe manifestations in AIDS patients, and subsequently improved diagnostic methods were developed .…”
mentioning
confidence: 99%